2021
DOI: 10.1002/hbm.25574
|View full text |Cite
|
Sign up to set email alerts
|

Improving the predictive potential of diffusion MRI in schizophrenia using normative models—Towards subject‐level classification

Abstract: Diffusion MRI studies consistently report group differences in white matter between individuals diagnosed with schizophrenia and healthy controls. Nevertheless, the abnormalities found at the group‐level are often not observed at the individual level. Among the different approaches aiming to study white matter abnormalities at the subject level, normative modeling analysis takes a step towards subject‐level predictions by identifying affected brain locations in individual subjects based on extreme deviations f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…As ASD is mostly classified as HC compared to other schizophrenia spectrum groups, the neuroanatomical changes used in the classifier during early clinical stages are specific to schizophrenia and weighed both differences in trait and progressions in brain pathology. Recent studies including whole brain (gray matter, white matter, and ventricular cerebrospinal fluid volumes) 33 or diffusion MRI as features reported a high performance rate 32 , 34 ; with more features, it is possible to achieve a higher accuracy with relatively smaller samples than this study.…”
Section: Discussionmentioning
confidence: 61%
“…As ASD is mostly classified as HC compared to other schizophrenia spectrum groups, the neuroanatomical changes used in the classifier during early clinical stages are specific to schizophrenia and weighed both differences in trait and progressions in brain pathology. Recent studies including whole brain (gray matter, white matter, and ventricular cerebrospinal fluid volumes) 33 or diffusion MRI as features reported a high performance rate 32 , 34 ; with more features, it is possible to achieve a higher accuracy with relatively smaller samples than this study.…”
Section: Discussionmentioning
confidence: 61%
“…Differences in volume and structure were also found at the white matter, correlated with significant cortical deficits. Imaging research, based on the latest technologies, has revealed numerous white matter abnormalities [ 116 , 117 ]. One of the novel findings of this research was the increase in the volume of extracellular water.…”
Section: Anatomical Changes and Their Impactmentioning
confidence: 99%
“…Each location collected site-specific schizophrenia participant populations and healthy controls with similar distributions of age and sex. Imaging and clinical data from this harmonized cohort has been previously published [5,[20][21][22]. A detailed description of the data collection and subsequent quality control procedures performed to attain to the final sample for the present study can be found in the Supplement (Section: Data Collection and Quality Control).…”
Section: Participantsmentioning
confidence: 99%
“…Therefore, we applied a dMRI data harmonization technique developed by our group to remove site-, sequence-, and scanner-specific effects from the dMRI data, while preserving inter-subject biological variability [19]. We have successfully validated and applied our harmonization framework in multiple studies [5,[20][21][22][23][24][25][26], including a recent study using FA, which revealed patterns of age-related white matter pathology in individuals with schizophrenia [5].…”
Section: Introductionmentioning
confidence: 99%